The Russian oil exports via the Baltic sea ‐ do oil shipments through the EU's inner sea bring Russia closer to the EU or bring them apart? - Liuhto, Kari (Journal of Business Economics and Management, 2003)
The paper deals with Russian oil exports policy. Russia's oil reserves, oil production and main export routs have been scrutinized and evaluated.First Published Online: 14 Oct 2010